126k views
0 votes

- 9 - ( - 4) =
i don't know



2 Answers

2 votes

Answer:

- 9 -( -4) = -5

Explanation:

-9-(-4)

solve the one in the bracket first because there is a minus sign between 9 and the bracket so we cannot use the 9 to multiple the number four in the bracket.

-9+4

the sign has changed to positive because when negative numbers are multiplying each other to will turn in to become positive.

so -9+4= -5

solution.

-9-(-4)

-9+4

-9+4= -5

therefore the answer is -5.

User Dave Andersen
by
6.4k points
0 votes


\sf\purple{-5}

Explanation:


- 9 - ( - 4) \\ = - 9 + 4 \\ = - 5

Note:-


\sf\red{(-)\:x\:(-)\:=\:+}


\large\mathfrak{{\pmb{\underline{\orange{Happy\:learning }}{\orange{.}}}}}

User Arnaud Denoyelle
by
6.2k points